TNF‐α Has Tropic Rather than Apoptotic Activity in Human Hematopoietic Progenitors: Involvement of TNF Receptor‐1 and Caspase‐8123. (19th December 2012) - Mizrahi, Keren; Stein, Jerry; Yaniv, Isaac; Kaplan, Offer; Askenasy, Nadir
Abstract Tumor necrosis factor‐α (TNF‐α) has been suggested to exert detrimental effects on hematopoietic progenitor function that might limit the success of transplants. In this study, we assessed the influences of TNF‐α and its two cognate receptors on the function of fresh umbilical cord blood (UCB) and cryopreserved mobilized peripheral blood (mPB). CD34+ progenitors from both sources are less susceptible to spontaneous apoptosis than lineage‐committed cells and are not induced into apoptosis by TNF‐α. Consequently, the activity of UCB‐derived severe combined immune deficiency (SCID) reconstituting cells and long‐term culture‐initiating cells is unaffected by this cytokine. On the contrary, transient exposure of cells from both sources to TNF‐α stimulates the activity of myeloid progenitors, which persists in vivo in UCB cell transplants. Progenitor stimulation is selectively mediated by TNF‐R1 and involves activation of caspase‐8, without redundant activity of TNF‐R2. Despite significant differences between fresh UCB cells and cryopreserved mPB cells in susceptibility to apoptosis and time to activation, TNF‐α is primarily involved in tropic signaling in hematopoietic progenitors from both sources. Cytokine‐mediated tropism cautions against TNF‐α neutralization under conditions of stress hematopoiesis and may be particularly beneficial in overcoming the limitations of UCB cell transplants. Stem Cells2013;31:156–166